The Effect of Using Blue Light Filter Feature on Smartphones with Asthenopia Occurrence - Arnan Victor Wiryawan; Maharani Maharani; Tanti Ajoe Kesoema; Riski Prihatningtias (Faculty of Medicine, Diponegoro University, 2021)
Background: Smartphone users can be found in almost every class society in Indonesia. Excessive use of smartphones and the blue light emitted by smartphones play an important role in causing asthenopia symptoms. Smartphone development companies have developed a blue light filter feature, which is expected to reduce the incidence of Asthenopia symptoms.Objective: To evaluate the Asthenopia questionnaire's comparison results before and after smartphone use with various levels of opacity in the blue light filter.Methods: This study used a quasi-experimental pre-posttest study. The research subjects were students of the Faculty of Medicine, Diponegoro University (n = 30), selected by purposive sampling. In this study, research subjects saw an hour-long smartphone with a predetermined opacity level for the blue light filter, with the same room lighting. Before and after the treatment, the subjects were asked to fill out the Asthenopia questionnaire. Data were analyzed using the Wilcoxon test, Mann Whitney U test, and Kruskal Wallis test.Results: The results of the Asthenopia questionnaire before and after using a smartphone with a blue light filter opacity level of 0% and 100% showed a significant difference in results (p <0.05), and there was no significant difference for the pre-posttest using a smartphone with a blue light filter with 50% opacity level. The comparison results of the Asthenopia questionnaire between smartphone use with the opacity level of the blue light filter 0% and 50% only showed a significant difference in sore/aching eye symptoms. The comparison results of the Asthenopia questionnaire between smartphone use with the opacity level of the blue light filter 50% and 100% only showed a significant difference in sleepy eye symptoms. The comparison results of the Asthenopia questionnaire between smartphone use with the opacity level of the blue light filter 0%, 50%, and 100%, did not show a significant difference.Conclusion: There were no significant differences between the Asthenopia questionnaire results with 0%, 50%, and 100% opacity blue light filters after one hour of smartphone use.